2016
DOI: 10.1177/1049909115605058
|View full text |Cite
|
Sign up to set email alerts
|

Conclusiveness of the Cochrane Reviews in Palliative and Supportive Care for Cancer

Abstract: To assess the conclusiveness of the Cochrane reviews (CRs) in the field of palliative and supportive care for cancer. We searched the CRs on Pain, Palliative, and Supportive Care Group available in the Cochrane library on February 01, 2015, to analyze whether a CR could reach a clinical decision. Each CR was analyzed for conclusiveness, number of randomized controlled trials (RCTs) enrolled, number of participants enrolled, the need for further studies, and the reasons. Only 45% (30 of 66) of the CRs reached d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“… 5 Findings from previous analyses of Cochrane reviews in other medical specialties have varied, with some reporting a large proportion of conclusive reviews, 6 , 7 whereas others were more likely to be inconclusive. 8 , 9 The total number of studies and total number of included participants were associated with review conclusiveness. 6 9 It is important to note that these previous studies of the conclusiveness of Cochrane reviews did not evaluate reviewers’ judgements about the quality of evidence.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Findings from previous analyses of Cochrane reviews in other medical specialties have varied, with some reporting a large proportion of conclusive reviews, 6 , 7 whereas others were more likely to be inconclusive. 8 , 9 The total number of studies and total number of included participants were associated with review conclusiveness. 6 9 It is important to note that these previous studies of the conclusiveness of Cochrane reviews did not evaluate reviewers’ judgements about the quality of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it would be useful if systematic reviews would provide clear conclusions and recommendations. Although there are studies available that investigated the conclusiveness of Cochrane reviews from specific fields [ 17 , 18 ] to the best of our knowledge, there are no large-scale studies about the conclusiveness of Cochrane PLSs in the published literature.…”
Section: Introductionmentioning
confidence: 99%
“…This is inconsistent with previous analyses of CRs in different fields. There were 61 CRs (with 30 conclusive) 9 on palliative and supportive care and 283 CRs (with 16 conclusive) 2,3 on physiotherapy. Moreover, we showed that clinical nurses cannot necessarily turn CRs into definite answers in family nursing.…”
Section: Discussionmentioning
confidence: 99%